044 Establishing an asparaginase monitoring assay to inform continuous care of patients with acute lymphoblastic leukaemia. (December 2018) - Lambert, J; Burke, D; Heales, S; Samarasinghe, S
Abstract : Background: Asparaginase is an important component of therapy for acute lymphoblastic leukaemia (ALL) due to the anti-neoplastic effect in patients. Allergic reaction to the foreign protein may lead to inactivation. Enzyme neutralization in the absence of apparent symptoms, termed silent inactivation, represents a significant threat to patient well-being. There is a need to monitor activity in patients to optimise dosage and prevent relapse. Our aims were to establish a monitoring assay and assess utility by measuring serial activity in patient serum. Methods: In the Department of Chemical Pathology, Great Ormond Street Hospital (GOSH), a colorimetric assay based on the method described by Lanvers et al (2002) was established and verified. Twenty children newly diagnosed with ALL and commencing the ALL2011 UK treatment protocols were recruited by the Department of Haematology and Oncology, GOSH. Serum samples were collected at various time points after enzyme administration and assayed. Results: Asparaginase activity in 13 patients remained above the therapeutic threshold (>100 U/L) up to 14 days after treatments, without apparent allergic reaction. Two patients exhibited severe immune reaction: serum activity was consistent with the clinical picture in one patient. Four patients displayed undetectable activity less than 14 days after treatment delivery, possibly suggesting silent inactivation. One patient showed activity considerably below therapeutic threshold 12 days after treatment and may benefit from increased dose. Conclusion: In conclusion, the patient study demonstrated the clinical utility of the assay in children with ALL. Findings suggested 20% of patients may exhibit silent inactivation of the enzyme, a potentially high incidence that warrants a larger scale trial to further investigate and correlate activity with clinical outcomes. This study also demonstrates the value of inter-departmental collaboration within GOSH to potentially improve the quality of continuous care for patients.